Automatic design, optimization and In-Situ Fabrication of Heterogeneous Swarm Robot bodies using 3-D printing and multi-objective evolutionary algorithms - Teo, Jason Tze Wi; Johnny Koh; Chin, Kim On; Chua, Bih Lii; Willey Liew; Noor Ajian Mohd. Lair; Lim, Shun Hoe (Universiti Malaysia Sabah, 2012)
Over the last decade, various mobile robots have been developed and widely used in myriad sectors. However, the vast majority of mobile robots are manually designed where the designers must have the preliminary knowledge of the interaction between the robots and the environment. Additionally, the high complexity involved in the design of the kinematics and controllers of a mobile robot has always been the biggest challenge for researchers and practitioners alike. Thus, the task of designing a robot can be considered very demanding and extremely challenging. In this research, an artificial evolution approach utilizing Single-Objective Evolutionary Algorithm (SOEA) and Multi-Objective Evolutionary Algorithm (MOEA) respectively are investigated in the automatic design and optimization of the morphology of a Six Articulated-Wheeled Robot (SAWR) with climbing ability. Results show that the SOEA is able to produce optimized SAWR with climbing ability while the MOEA is able to produce a set of Pareto optimal solutions which provide users with a choice of solutions for trade-off between the objectives of morphology size and climbing performance. The Pareto optimal set of solutions are the smallest SAWR with the least climbing ability to the biggest SAWR with the best climbing ability. The research continues by transferring the evolved solutions from simulation to the real world using 30 printing. The body, legs and wheels of the evolved robots are printed by a 30 printer and assembled with sensors, servos and motors for real world testing. Results show that the fabricated real world SAWRs were able to perform the climbing motion with an average accuracy of 80.9% compared to the performance in simulation.